2017
DOI: 10.1002/slct.201701989
|View full text |Cite
|
Sign up to set email alerts
|

Access of Diverse 2-Pyrrolidinone, 3,4,5-Substituted Furanone and 2-Oxo-dihydropyrroles Applying Graphene Oxide Nanosheet: Unraveling of Solvent Selectivity

Abstract: Eco benign catalyst graphene oxide (GO) has been effectively exploited in one pot synthesis of 2‐pyrrolidinone, 3,4,5‐substituted furanone and 2‐oxodihydropyrrole derivatives, three important pharmacophores, via one‐pot domino reactions (MCR) among easily accessible amines, aldehydes and acetylinic esters. These small heterocyclic molecules have been well diversified employing a wide variety of amines and aldehyde derivatives establishing the broad catalytic activity of graphene oxide towards the synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…In this case, the nucleophilic addition of aromatic amines to the activated alkyne gives rise to a deactivated enamine intermediate and 0.5 equivalents of benzoic acid are required in order to promote the subsequent Mannich reaction [30]. Activation of this process was also described by the use of molecular iodine [31] or graphene-oxide nanosheets under solvent-free conditions [32]. In this context, organocatalysis is identified to be at the heart of greening of chemistry, because this branch of science is found to reduce the environmental impact of chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the nucleophilic addition of aromatic amines to the activated alkyne gives rise to a deactivated enamine intermediate and 0.5 equivalents of benzoic acid are required in order to promote the subsequent Mannich reaction [30]. Activation of this process was also described by the use of molecular iodine [31] or graphene-oxide nanosheets under solvent-free conditions [32]. In this context, organocatalysis is identified to be at the heart of greening of chemistry, because this branch of science is found to reduce the environmental impact of chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, furan‐2‐ones have been prepared by employing β‐cyclodextrin, SnCl 2 .2H 2 O, ZnO nanoparticles, [Bu 4 N][HSO 4 ], sucrose, N ‐methyl 2‐pyrrolidonium hydrogen sulfate ([ H ‐NMP]HSO 4 ), SnO nanoparticles, HY Zeolite nano‐powder, watermelon juice, barberry juice, Vitamin B12, and graphene oxide (GO) as catalysts. Moreover, for the synthesis of pyrrol‐2‐ones, literature shows several methods with different catalysts which include acetic acid, I 2 , 1‐methyl‐2‐oxopyrrolidinium hydrogen sulfate ([Hpyro][HSO 4 ]), Cu(OAc) 2 ⋅H 2 O, TiO 2 nanopowder, trityl chloride, [n‐Bu 4 N][HSO 4 ], InCl 3, (S)‐camphorsulfonic acid, nanoZnO, vitamin B12, ethylenediammoniumdiformate (EDDF), 2,6‐pyridinedicarboxylic acid, UiO‐66‐SO 3 H metal‐organic framework, magnetic metal‐organic framework‐based catalyst CoFe 2 O 4 @SiO 2 @IRMOF‐3, Fe 3 O 4 @nano‐cellulose‐OPO 3 H, N,N,N,N ‐tetramethyl guanidinium acetate [TMG][Ac], graphene oxide (GO) etc . Despite the effectiveness of these catalysts, the usage of some of these methods are allied with several short comings such as harsh reaction conditions,, use of stoichiometric amounts of catalysts, prolonged reaction time,,,, difficulty in product isolation,,, and co‐occurrence of side reactions.…”
Section: Introductionmentioning
confidence: 99%
“…A search of the Cambridge Structural Database (CSD Version 5.42, update of November 2020; Groom et al, 2016) for the 3hydroxy-1,5-dihydro-pyrrol-2-one fragment revealed 79 hits. Only 27 of these hits contain a fragment with the same structure as that of the title compound [refcodes: BOQXEN (del Corte et al, 2019), CIKPAQ (Sarkar et al, 2018), EVIYUD (Aliev et al, 2003b), GEJZAY (Mashevskaya et al, 2011), GIMGEQ (Sarkar et al, 2013), GITCAQ, GITDEV (Saha et al, 2017), IRUBUS (Aliev et al, 2003a), LIFBEJ, LIFBOT (Sun et al, 2011), NUXPIG (Wiedemann et al, 2009), PADHUA (Zonouz et al, 2015), PASTOT (Nicolaou et al, 2005), QIPNAH (Bhajammanavar et al, 2019), ROHNAG (Hosseinzadeh et al, 2019), TOMPER (Sakhno et al, 2008), UJEXOY (Ahankar et al, 2016), VILQEP (Gein et al, 2018), VIPNAJ (Mylari et al, 1991), VIQDOP (Guseinov et al, 2006), VOWGAP (Kazakov et al, 1990), WAPMIM (Dubovtsev et al, 2016), XINHIL (Aliev et al, 2001), XOKRAT, XOKRAT01 (Ramazani et al, 2019), YAJMOM (Wei et al, 2004), YIYFAP (Denislamova et al, 2014)]. All these structures and the title compound have the same electron density distribution within the 3-hydroxy-1,5-dihydropyrrol-2-one fragment.…”
Section: Database Surveymentioning
confidence: 99%